Penerapan Metode Tutor Sebaya Untuk Meningkatkan Hasil Belajar Pendidikan Agama Hindu Pada Siswa Kelas III Sekolah Dasar Negeri 1 Sukadana - Ni Luh Adi Palistini (Jurnal Penjaminan Mutu, 2018)
The purpose of this study is: to know the results of student learning through the application of Peer Tutor method in grade 3 students of Primary School Negeri 1 Sukadana.Penelitian is Classroom Action Research conducted in two cycles, each consisting of four stages: planning, observation, reflection. The research subjects are the third grade students of SD Negeri 1 Sukadana which amounted to 24 people. The method used is a test method to collect data on student learning outcomes. After all collected, the data is analyzed descriptively quantitative. Data analysis in this research using quantitative descriptive. The results showed the students' learning outcomes in the first cycle average score of learning outcomes with low categories. The average value of student learning outcomes in the first cycle is 77.08 with 66.66% classical completeness, absorption 77.08%. Then on the second cycle has increased, the average learning outcome becomes 82.29 classical completeness to 91.66% and absorption to 82.29%. And result of analysis of learning result of cycle I and II have increase of average value of result of learning equal to 5,21 classical completeness equal to 25% absorption equal to 5,21% with use of peer tutor method. Based on the results of this study can be concluded the use of peer tutors can improve learning outcomes Hindu Religious Education. (1) Hindu Education Teachers to try to apply the use of peer tutors (2) Other researchers are expected to conduct further research related to the application of innovative learning models.